Olfactory training ball improves adherence and olfactory outcomes in post-infectious olfactory dysfunction - Saatçi, Özlem; Altundağ, Aytuğ; Arıcı Düz, Özge; Hummel, Thomas (Springer, 2020)
Purpose In an effort to make olfactory training (OT) simpler, we designed an 'olfactory training ball' (OTB)-a baseball-size ball with four odor-containing tubes to use in OT. The study aimed to investigate the effects of OT with the OTB in comparison to classical OT with special attention to the effects of adherence to OT on olfactory outcome measures. Methods Sixty patients with olfactory dysfunction following infections of the upper respiratory tract received OT either with classical methods-sniffing odors from jars (COT)-or the OTB for 12 weeks. Patients exposed themselves to the odors for 5 min twice daily. Adherence was measured with a modified version of the Morisky scale. Before and after OT, all patients underwent extensive olfactory testing using the Sniffin' Sticks test. Results At the end of the 12 weeks of OT, TDI composite score (22.1 +/- 2.8 vs. 19.9 +/- 4.7, P = 0.044) and odor discrimination subtest scores (9.1 +/- 1.8 vs.7.6 +/- 2.5, P = 0.013) of the OTB group were significantly higher than that of the COT group. Adequate adherence to OT was significantly higher in patients receiving OTB when compared to those receiving COT (63% vs. 30%, P = 0.019). Conclusion The present study shows that a novel OT device, the OTB, provides better adherence to the training process compared to COT. Moreover, findings of the current study show that better adherence to the OT process is associated with better olfactory outcomes.
Keywords: Olfaction; Smell; Olfactory Training; Olfactory Training Ball